1984
DOI: 10.1099/00207713-34-4-393
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus piscicola, a New Species from Salmonid Fish

Abstract: The name Lactobacillus piscicola sp. nov. is proposed for a group of 17 bacterial strains that were isolated from diseased rainbow trout (Salmo gairdneri), cutthroat trout (Salmo clarki), and chinook salmon (Oncorhynchus tshawytscha). This bacterium was found most frequently in infected fish which had suffered some form of stress, such as that which occurs at spawning. Occasionally, pathological signs in the internal organs or skin were observed. Phenotypically, L . piscicola belongs to the family Lactobacilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 34 publications
(22 reference statements)
2
82
0
Order By: Relevance
“…piscicola in the same DNA homology group was unexpected. Biochemical and chemical data, however, reinforce this relatedness and indicate that these species should be reduced to synonymy (the specific epithet piscicola [9] has priority over carnis [19,201). The biochemical and nucleic acid data showed that the remaining group 2 strains were unrelated to the other species examined and warrant separate specific status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…piscicola in the same DNA homology group was unexpected. Biochemical and chemical data, however, reinforce this relatedness and indicate that these species should be reduced to synonymy (the specific epithet piscicola [9] has priority over carnis [19,201). The biochemical and nucleic acid data showed that the remaining group 2 strains were unrelated to the other species examined and warrant separate specific status.…”
Section: Discussionmentioning
confidence: 99%
“…nov. The full description of C. piscicola is as given by Hiu et al (9) but should be extended and emended as follows. Under certain conditions exhibits heterofermentative properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C18: 1 compound is a cis9,12 isomer. Members of the genus Carnobacterium have been isolated from a wide range of environments such as refrigerated meat products (Monte1 et al, 1991), salmonid fish (Hiu et al, 1984) and anoxic lake water in Antarctica (Schroder et al, 1980). They are difficult to distinguish from Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…mobile, which were isolated from poultry (Thornley and Sharpe 1959). Carnobacterium piscicola strains have also been recognized as fish pathogens (Hiu et al 1984;Baya et al 1991;Starliper cl al. 1992).…”
Section: Introductionmentioning
confidence: 99%